Acquisition and processing of biological multi-spectral images: a case of study in cardiovascular tissue (Revista de Investigaciones Universidad del Quindío, 2016)
This article presents the use of multispectral acquisition and processing techniques in the analysis of biological tissue, specifi cally cardiovascular one. Different kinds of architectures are presented, like those based on interference fi lters and those that do not require the use of such as fi lters. Advantages and disadvantages of both systems are also presented, as well as techniques for color calibration and sources of noise. Also, two kinds of image processing techniques in biological images are presented: Principal Component Analysis (PCA) and Independent Component Analysis (ICA). Those techniques have been used in the analysis of biological images such as human skin, and colon. However, and up to our knowledge, those techniques have not been widely used in the analysis of cardiovascular tissue, so that special focus is done in this specifi c application. As a result, it is found that PCA and ICA methods allow obtaining images with a better defi nition of cardiovascular tissue morphology.
Keywords: cardiovascular tissue; principal component analysis (PCA); independent Component Analysis (ICA)